A Influência na consolidação de cargas e nos prazos de entrega decorrentes da alteração da modalidade de frete: um estudo de caso em uma refinaria de petróleo no Estado do Ceará - Leal, Marcus Costa Lima Verde (2015)
The oil and gas sector in Brazil is quite heated, mainly by investment in the production of the layer of pre-salt and the construction of new refineries. This case study of quantitative nature, aimed to assess how the change in the form of freight charges for purchases of materials made by an oil refinery in the state of Ceara will enable the increasement of workloads consolidation and the reduction of the time limits for delivery of these materials, as well as to propose a procurement system that offers a solution to the problem.The data collection was carried out through two instruments: a survey of data for the purchase of materials made for the refinery during the year of 2013 and a semistructured questionnaire, sent to the main suppliers.To analyze the quantitative results of the study, it was used the software Statistical Package for Social Sciences (SPSS), version 19.0.It was proposed as a system of purchases the carrying out of the acquisitions in the modality FCA, in which materials would be collected by a contracted carrier for the refinery tank supplier.The results show that the change in the modality of freight, from DDP to FCA, may cause a reduction in delivery time up to five days, although it does not make a large increasement in consolidation of workloads.The study was also able to verify that this change may cause a reduction close to 1% in the cost of transport for loads of a value around R$ 1,000.00, in addition to other secondary gains, such as reducing the amount of carriers that would access the refinery, with a consequent reduction of the administrative effort to receive and care for carriers